Impact of initial and preschool education in children’s neurodevelopment - Gutiérrez Duarte, Socorro Alonso; Ruiz León, Mara (IE Revista de Investigación Educativa de la REDIECH, 2018)
Significant research has shown that during the first years of life the fundamentals of neurophysiological character that will determine the higher psychological processes are structured. At the same time, they guarantee the quality of educational programs and living conditions are of paramount importance; it is known that it’s the stage where brain functions that are related to sensory development and language are built. The objective of this study is focused on determining statistically significant differences in neurodevelopment of children who have participated in programs of early childhood education and those who were enrolled just in preschool education; the methodology used is part of the quantitative paradigm with a non-experimental cross-sectional design and descriptive type. The subjects in the research were third-grade preschool children from Hidalgo del Parral, Chihuahua. Contextual characteristics are very different; there are groups living in extreme poverty, as there are in high economic status. The results indicate that children who attend Children’s Centers since their birth as those who live in enriched and flattering contexts have a higher level of neurodevelopment.